Miopia sebagai Faktor Risiko Terjadinya Penurunan Prestasi Belajar pada Anak SDN Cemara Dua Surakarta - Indrakila, Senyum; Primadewi, Novi (Nexus Kedokteran Klinik, 2014)
Background: Academic achievement is result of learning, which can be obtained by test. It is influenced by many internal factors (including five senses condition) and external factors. When there was an abnormality in the eye (including myopia), it will influence the learning procces, so the children cant get their best academic achievement. This study has a purpose to know if myopia is a risk factor for decreased academic achievement in children at SDN Cemara Dua Surakarta. Methods: This study is a case control study, conducted at SDN Cemara Dua Surakarta. Sample is divided into 2 groups (case group and control group) based on progress of academic achievement by end-semester report in year 2012/2013 (decreased or still/increased). And then refraction test by noncycloplegic autorefractometer is done to know myopia state of children. Independent variable is myopia, dependent variable is decreased academic achievement, and confounding factors are sex and tutoring. This study uses Chi-Square and multiple logistic regression to analyse data. Results: Students with myopia have probability 0.714 less than students without myopia to have a decreased academic achievement, but this relationship is not significant. (OR = 0.714; Cl 95% 0.252 s.d. 2.025; p = 0.525). Multiple logistic regression is not done because based on result of Chi-Square, confounding factors have p > 0.25 (sex p = 0.701, tutoring p = 0.750). Conclusions: Relationship between myopia and decreased academic achievement is not significant, so myopia is not a risk factor of decreased academic achievement in children at SDN Cemara Dua Surakarta. Keywords: Myopia, decreased academic achievement, case control, noncycloplegic autorefractometer. Â